The domestic battle over the design of non-trade issues in preferential trade agreements. Issue 5 (2nd September 2016) - Lechner, Lisa
ABSTRACT: Human rights, labour standards, and environmental protection standards are commonly linked to trade. Because these links come in different forms, the question arises: what accounts for such variation? An examination of the wide variety of non-trade issues (NTIs) in preferential trade agreements (PTAs) reveals that prominent explanations fall short of explaining this variation. I argue that domestic characteristics of trade partner countries trigger lobbying by interest groups and cause design changes. I hypothesize that strong import and wage pressure increases lobbying by social and environmental protection advocates. A large difference between member states regarding civil and political rights protection levels should trigger NGO activity, but only if at least one member complies at a very high level already. In order to test the argument, I rely on a novel dataset including newly coded data on NTIs design for 474 PTAs signed between 1990 and January 2016. The findings using multivariate regression analysis show that linking trade and social or environmental clauses is motivated by strategic and the inclusion of political rights by substantial interests. This study contributes to the literature on rational design of international institutions, legalization, and issue-linkage.